Processing of the seven valine tRNAs in Escherichia coli involves novel features of RNase P - Agrawal, Ankit (Oxford University Press, 2014)
Here we report that RNase P is required for the initial separation of all seven valine tRNAs from three distinct polycistronic transcripts (valV valW, valU valX valY lysY and lysT valT lysW valZ lysY lysZ lysQ). Particularly significant is the mechanism by which RNase P processes the valU and lysT polycistronic transcripts. Specifically, the enzyme initiates processing by first removing the Rho-independent transcription terminators from the primary valU and lysT transcripts. Subsequently, it proceeds in the 3′ → 5′ direction generating one pre-tRNA at a time. Based on the absolute requirement for RNase P processing of all three primary transcripts, inactivation of the enzyme leads to a >4-fold decrease in the levels of both type I and type II valine tRNAs. The ability of RNase P to initiate tRNA processing at the 3′ ends of long primary transcripts by endonucleolytically removing the Rho-independent transcription terminator represents a previously unidentified function for the enzyme, which is responsible for generating the mature 5’ termini of all 86 E. coli tRNAs. RNase E only plays a very minor role in the processing of all three valine polycistronic transcripts.